Reformasi Pendidikan Nasional - Sakila, Ade (Jurnal Dinamika Sosial Budaya, 2023)
This journal tries to describe common problems that often arise in the world of national education, especially in Indonesia. Education which was originally a bridge to realize a complete human being cannot be separated from various kinds of problems, ranging from problems of facilities and infrastructure, the gap between what is learned and taught in school With the problems of life that occur around, the irrelevant output of the world of education with the needs of the world of work , limited opportunities for education in schools to the sad fate of teachers as agents of change in educational institutions has always been a decoration of the mass media both print and electronic. To solve various kinds of problems, it is certainly not as easy as turning the palm of the hand, it takes awareness and cooperation of various parties so that these general problems can be eroded slowly, with the hope that the educational goals mandated by the founding fathers of the Indonesian nation can be realized. This journal, with all its limitations, tries to describe the various kinds of problems faced by the Indonesian people as well as offers steps to solve them